EFEKTIVITAS EDUKASI DAN TERAPI PERMEN NIKOTIN TERHADAP PENURUNAN PERILAKU MEROKOK REMAJA - Yessica; Natalia; Sumilat, Vervando (Fakultas Keperawatan, Universitas Katolik De La Salle Manado, 2023)
Introduction: Smoking is a phenomenal act that has now become a habit for most of the surrounding community, especially teenagers. In a cigarette there are several kinds of ingredients that are very dangerous for the health of the body, namely carbon monoxide, tar, and nicotine substances. Therefore, it is necessary to provide nursing action to minimize smoking behavior. The intended action is in the form of education or therapy that is useful for improving the quality of health for everyone. Objective: To determine the effectiveness of providing education and nicotine candy therapy on reducing adolescent smoking behavior. Methods: This study used a pre-experimental design with a one-group pre-test-post-test design approach. The population in this study amounted to 30 people, namely all of them who smoked in adolescents in Klabat Village, North Minahasa Regency. Sampling research using total sampling. Education was given once, after which 28 nicotine candies were given which the respondent consumed for 2 weeks. The instrument used was a smoking behavior questionnaire. Results: The results of the analysis using the Paired T-test found that the mean pre-test was 32.16 and the post-test decreased to 27.70. Meanwhile, the p-value was 0.000 (p-value < 0.05) so that Ho was rejected and Ha was accepted, meaning that there was a significant difference in the decrease in smoking behavior before and after the administration of education and nicotine gum therapy. Conclusion: Providing education on nicotine candy therapy is effective in reducing adolescent smoking behavior in Klabat Village, North Minahasa Regency.